WEARABLE E-TEXTILE INTEGRATED SENSORS FOR DETECTING HYPERKALEMIA AND HYPOKALEMIA - Nageshwari Raja; Maheswaran Easwaran (Kongunadu Research Journal, 2025)
Recent evolutions in wearable and personalized healthcare devices have led to the emergence of real-time monitoring of the physiological and metabolic status of human beings. Detection of disorders related to potassium levels including hyperkalemia and hypokalemia is very much challenging in the current scenario. Potassium imbalance leads to massive change in electrical activity of the body especially disturbs the function of the brain, heart, nerves, bone and muscles in hospitalized patients. Potassium loss is a major concern in disorders such as hyperhidrosis and Cystic Fibrosis. Hence the real-time monitoring of potassium levels in the hospitalized patients may provide information related to latent cardiac problems and also assist in the diagnosis of apparent life-threatening diseases. Comprehensively, the real-time monitoring of potassium concentrations may shed light on the electrolyte loss, dehydration status and also the other associated diseases. In this study, the correlation between the Electrocardiogram (ECG) signals and the potassium levels can diagnose the potassium imbalance in a non-invasive manner. The novelty of our work is to develop a wearable E-textile integrated sensor for the detection of hyperkalemia and hypokalemia through ECG signal. The main advantage of this product is wearable and portable, and also ensures the patient safety and user friendly particularly for elderly and disabled patients and also for children.